2013
DOI: 10.1377/hlthaff.2012.1300
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence That Primary Care Physicians Offer Less Care To Medicaid, Community Health Center, Or Uninsured Patients

Abstract: The Affordable Care Act increases US investment in Medicaid and community health centers, yet many people believe that care in such safety-net programs is substandard. Using data from more than 31,000 visits to primary care physicians in the period 2006-10, we examined whether the length or content of a visit was different for safety-net patients-those insured by Medicaid, those who are uninsured, and those seen in a community health center-compared to patients with private insurance. We found no significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
19
1
1
Order By: Relevance
“…Other factors can affect the time actually spent, including longer appointment blocks that some clinics use for new patients and those scheduled for yearly check-ups or complex visits. Still, the results of our study and others 19,33 find that visit length for all provider types averages very near twenty minutes per patient. When patient needs require additional time, providers typically schedule return appointments to address those needs.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Other factors can affect the time actually spent, including longer appointment blocks that some clinics use for new patients and those scheduled for yearly check-ups or complex visits. Still, the results of our study and others 19,33 find that visit length for all provider types averages very near twenty minutes per patient. When patient needs require additional time, providers typically schedule return appointments to address those needs.…”
Section: Discussioncontrasting
confidence: 51%
“…A recent analysis of primary care visits by Bruen and colleagues using NAMCS data found that care of CHC patients was similar to that of patients in other settings with regard to content of care and time spent per visit. 33 Like the Bruen group, we found that the major determinants of time spent with patients were their health needs and the type and quantity of care provided. The organization of care and characteristics of providers are different in CHCs than in the private sector, and these differences might also limit generalizability of our findings.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As demand for care grows, time spent in the waiting room has come to exceed time spent with a physician on average [5,19]. While this fact is frustrating for providers and patients alike, it also challenges those in the system to rethink the waiting room space and time, to imagine new possibilities for it, and to incorporate it into the system of care provision as a tool, not a necessary evil.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Community health centers (CHCs) provide primary care to medically underserved and vulnerable populations regardless of ability to pay. 7 Most CHC patients are uninsured or Medicaid recipients, and have incomes below the FPL. 8 CHCs are well positioned to identify patients who smoke and to provide them with smoking cessation assistance.…”
Section: Introductionmentioning
confidence: 99%